Eco-friendly Alkyd Resins Based on Vegetable Oil: Review - Okta Amelia; Illah Sailah; Ika Amalia Kartika; Ono Suparno; Yazid Bindar (Jurnal Rekayasa Proses, 2021)
The alkyd resin industry currently needs environmentally friendly raw materials, which emphasized the aspect of sustainability. Alkyd resin is a polymer product with oil as raw material which is widely used in the paint, coating, and other industries. The abundant demand for alkyd resin has led to a diversification of the raw material for alkyd resin from vegetable oils. The advantages of vegetable oil include being a renewable energy source for industry, sustainability, biodegradability, and being environmentally friendly as important considerations for the industry in recent times. This paper examines alkyd resins derived from several vegetable oils that are environmentally friendly. Alkyd resin is prepared by alcoholysis and esterification. Based on several studies of alkyd resins, there have been many modifications to the raw materials, technology, and catalysts used which can refer to an environmentally friendly and affordable industry.Keywords: alkyd resin; biodegradability; environmentally friendly; sustainability; vegetable oilA B S T R A KIndustri polimer pada masa ini membutuhkan bahan baku yang ramah lingkungan, yang menekankan pada keberlanjutan. Alkid resin adalah salah satu produk berbasis minyak yang banyak digunakan dalam industri cat, coating, dan industri lainnya. Keberlanjutan, biodegradabilitas, dan keramahan terhadap lingkungan menjadi pertimbangan signifikan bagi industri berbasis minyak nabati dalam beberapa waktu terakhir. Di dalam naskah ini, diulas beberapa minyak nabati yang digunakan untuk memproduksi alkid resin dengan cara alkoholisis dan esterifikasi. Berdasarkan berbagai studi yang telah dilakukan, masih terdapat modifikasi dari sisi material, teknologi dan katalis agar tercipta industri yang ramah lingkungan.Kata kunci: alkid resin; biodegradabilitas; keberlanjutan; minyak nabati; ramah lingkungan